The Ambiguous Uses of History, Memory and the Archive - Kingman, Eduardo (2012)
This text, which parts from the last issue of Íconos, “Rethinking the Archive,” addresses the complex relationship between history, memory and the archive. The text is not a criticism but rather a comment whose purpose is to discuss some of the tendencies in perceiving these relationships: 1) assuming there is only one way of producing history and thus only one way of relating to the archive 2) failing to differentiate one type of archive from another, thus failing to avoid the so-called archive fever 3) confusing history and memory, or rather separating one from another without finding commonalities between both 4) conceiving memory solely in relation to historiography (or anthropology) without acknowledging its role in fields such as film or contemporary art.